In-situ growth of nitrogen-doped carbon nanotubes on MXene nanosheets for efficient sodium/potassium-ion storage - Wang, Tao; Zeng, Jinjue; Gu, Xianrui; Meng, Yuhang; Yang, Han; Zhu, Hongda; Deng, Dingfei; Sun, Zhipeng; Ding, Rui; Li, Yongle; Rong, Junfeng; Wang, Xuebin (Frontiers in Materials, 2023)
For game changing for future of large-scale energy storage technologies, sodium-ion and potassium-ion batteries provide a substitute to lithium-ion batteries. As an excellent candidate anode, MXene still suffers from the blockage of active sites caused by restacking of sheets. Herein, an in-situ decoration of MXene nanosheets with nitrogen-doped carbon nanotubes (CNTs) is introduced, to yield MXene@CNTs. The modification of nitrogen-doped CNTs not only prevents the restacking of MXene and increases ion accessibility but also improves the electrode's overall conductivity, thereby enhancing electron conduction and ion diffusion kinetics significantly. Therefore, MXene@CNTs exhibits superior sodium/potassium-ion storage performance than pure MXene nanosheets. At 0.05 A g-1, it can deliver reversible capacities of 286 mAh g-1 for SIBs and 250 mAh g-1 for PIBs. This research illustrates the significance of the electrode architecture for electrochemical performances, and the in-situ growth strategy could provide some insight on searching for high-performance MXene-based anodes for SIBs and PIBs.